Treatment Fidelity in a Randomized Controlled Trial of Cognitive Behavioral Therapy for Insomnia in Heart Failure. Issue 6 (20th November 2022) - O'Connell, Meghan; DeSanto Iennaco, Joanne; Linsky, Sarah; Jeon, Sangchoon; Conley, Samantha; Gaiser, Edward; Redeker, Nancy S.
Abstract : Background: Cognitive behavioral therapy for insomnia (CBT-I) is an efficacious treatment for people with chronic insomnia, including those with heart failure (HF). Treatment fidelity evaluation is needed to ensure study validity and reliability. Objective: The aim of this study was to apply the National Institutes of Health Behavioral Change Consortium framework to ensure adequate treatment fidelity in a randomized controlled trial of CBT-I for people with stable HF. Methods: We describe strategies to ensure treatment fidelity in study design, provider training, and treatment delivery. We measured treatment receipt (observation and self-report) and enactment of CBT-I strategies (self-report and actigraphy). We used the Dysfunctional Beliefs and Attitudes About Sleep Scale and the Sleep Disturbance Questionnaire to indicate sleep-related beliefs and cognitions. We computed descriptive statistics for demographic characteristics, treatment receipt, and enactment variables. We compared baseline and post-intervention dichotomous sleep behaviors using the two-sided Wilcoxon rank-sum test. We calculated the root mean square of successive difference in time of sleep onset and midpoint (actigraphy) to indicate day-by-day variability in bed and wake times. Results: Most participants completed the CBT-I intervention and follow-up assessments and attended each group or make-up session. Most correctly computed their sleep efficiency and completed their homework. Most participants used the sleep tracker and reported using strategies to improve their sleep schedules. There was a significant decrease in actigraph-measured light intensity during the 30 minutes and 1 hour before bedtime between baseline and post-intervention and no statistically significant changes in light intensity after waking or in nap frequency. Most of those who woke during the night got out of bed, consistent with recommendations. There were significant improvements on all of the Dysfunctional Beliefs and Attitudes About Sleep items and total score and all but one item on the Sleep Disturbance Questionnaire. Discussion: Preserved treatment fidelity may explain the large and sustained effects in people with HF found in our trial. Further research is needed to evaluate CBT-I's effectiveness and implementation strategies among people with HF in real-world clinical settings.